The impact of economic crisis and non-economic factors on the tourism industry in Zlatibor - Čerović, Slobodan; Knežević, Miroslav; Sekulović, Nataša; Barjaktarović, Dragoljub; Đoković, Filip (The European Journal of Applied Economics, 2015)
Tourism has recorded a favorable development trend in the previous decades. Despite the fact that it was occassionaly exposed to adverse effects of the crises caused by numerous economic and non-economic factors, tourism has managed to recover significantly faster and record a higher growth rate compared to the entire world economy. This paper analyses the effects of the economic crisis and other non-economic factors on tourist movements in Serbia during the period 2007-2014, with special emphasis on Zlatibor as a popular tourism destination. The aim of this paper is to show that the aforementioned crisis had a major impact on the movements of domestic and foreign tourists in Serbia and Zlatibor during the analyzed period. Based on the available data, research was conducted and the results showed that the economic factors primarily led to the reduction in the number of tourists in Serbia, while the economic crisis had more impact on domestic travel than on the movements of foreign tourists in our country.